Using Google form for Student Worksheet as Learning Media - Iqbal, Muhammad; Simarmata, Janner; Feriyansyah, F; Riana Suryanti Tambunan, Anna; Sihite, Onggal; Gandamana, Apiek; Noveri Eza, Gita; Kurniawan, Fauzi; Asiah, A; Rozi, Fahrur; Faisal, F; Free Unita Manurung, Imelda; et al. (International Journal of Engineering and Technology, 2018)
This study aims to describe the creation of student worksheets using Google forms. The problem in this study is how the steps for creating student worksheets through the Google form and the structure of the worksheet produced. The method in this study uses qualitative descriptive types. Research subjects are instructors who use the Google forms as learning media. The researchers obtained the data through observation, in-depth interviews, and review of various document sources. The results of the study illustrate the steps in making student worksheets having the stages of preparation, design, and implementation. Some forms of worksheets produced, namely narrative models, audio-visuals and links. Â Â